Evaluation Framework for an ERP System using Balanced Scorecard Approach - joshi, Sudhanshu (Gyan Management Journal, 2009)
Tte overall purpose of this study is to explore whether BSC can he a better indicator to measure ERP system perfarm
Keywords: Balance Scorecard; ERP